Control of active car suspension system based on 2PID and PSO Optimization - Hajer Emad; Ali Mary; Malik Mohammed Al (Zien Journals, 2022)
Active suspension systems are essential to improve vehicle performance and ride comfort under various road vibrations. Active suspension systems proved a better option compared to a passive suspension system. It has an actuator that produces a force that reduces the turbulence caused by road interference. The suspension in this research is controlled by a 2Proportional-Integral-Derivative (PID) and optimize the gains using the Particle Swarm Optimization (PSO) method. Three forms of road disturbances are studied one is sine and step input and a single and two bumps. Simulation results demonstrated the advantage of 2PID controllers-based PSO algorithm in terms of improving the dynamic performance of the active suspension system regarding to body acceleration position and deflection and provide good tire-road contact.
Keywords: Active suspension; PSO; PID controller; quarter car